Mahatma Gandhi Album : the great experimenter (1996)
[Dt.:] "Kamat's Potpourri" ist ein Fachportal, das in gemeinschaftlicher Arbeit der Familie Kamat kulturelle, geschichtliche, religiöse oder politische Themen im indischen Kontext mit wissenschaftlichem Anspruch aufbereitet. Das Unterportal "Mahatma Gandhi Album" bietet vielfältige, multimediale Informationen über das Leben und Werk Mohandas Karamchand Gandhis, z.B. eine kommentierte Liste kürzlich erschienener Fachartikel zu Gandhi, eine ausführliche Biografie, Bilder und Zitate. - [Engl.:] "Kamat's Potpourri" is a personal web page of the Kamat family, who provide various information on cultural, historical, religious or political subjects with an academic claim. The subportal "Mahatma Gandhi Album" offers a large amount of information in different multimedia forms on the life and works of Mohandas Karamchand Gandhi, e.g. a commented bibliography of recent academic publications on Mahatma Gandhi, (auto-)biographies, pictures and quotations